De Moskee van Djenné, morfologie en onderhoud van een Afrikaans monument (Bulletin KNOB, 1989)
The Mosque of Djenné, Mali, was first founded in the 14th century, destroyed in 1830 during a jihad (holy war) of the orthodox Peul population and rebuilt in 1907. In the city of Djenné the mosque, also called the Great Mosque, takes a dominant place on a higher level at the market place. Though typical and local architecture and materials are used, the mosque is in it origins a traditional and orthodox one with the Gibla-wall, the covered hall for praying in the eastern part of the building and an inner square. The east-facade, with the outer-side of the Gibla-wall is marked by three towers, the main tower being the Mirab-tower, the place where the Imam leads the sermon inside the mosque. Beams of palm-wood in the facade are used for climbing by the masons during the annual maintenance of the mosque. The inner hall has an irregular shape, measuring 50 x 26 meters, the roof being supported by 90 columns. The main entrances are at the north and the south side of the mosque. Especially the northern facade shows the traditional characteristics of the Sudan-gable with three pilasters, a palm-wood beam and seven pointed elements, the Sarafar Idye. The south entrance is more simple in its appearance, being the entrance of the people of the poor western part of Djenné. Like the other houses in Djenné, the front-part of the mosque, with the hall, is the area of the men. The inner square of the mosque and the arcade is, like the rear-part of the traditional house, the area of the women. In the exterior and the interior of the mosque there is a narrow relationship with the traditional architecture of the living-houses of Djenné with a unique unity between mosque and city. The mosque, built of sun-dried bricks and plastered with clay, needs every year its regular maintenance and repair of the damage, caused by rain and sun. This annual maintenance is a duty for the whole community of Djenné and means an important event in the social life of the city. It keeps up the traditions and skills of the well-organized masons guild of Djenné. Each part of the city is responsible for a certain part of the mosque and the several parts of the city start already preparing the fresh clay one month before the event. The repair and maintenance of the mosque has the character of an annual festival. Masons with their pupils are encouraged by the focal nobility, the old people, women and children. Young boys hurry to provide the workers with fresh clay, nobles give cigarettes, dates, sweets etc. The event, which takes two days, is announced at the Friday before by the Imam after a gathering of the representatives of each part of the city After the event the remaining fresh clay is available for everyone who needs for repair of his own house. The mosque not only plays an important monumental role in the city as a whole, but also in a social and practical way by the annual gathering of the people, by preserving traditions and skills and by delivering materials for repair of the traditional private houses.